Profil Literasi Membaca pada Materi Mitigasi Bencana di Sekolah Dasar - Rosniwaty Rosniwaty; Hendratno Hendratno; Nurul Istiq’faroh (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The importance of developing reading materials on disaster mitigation aims to equip students with knowledge on self-rescue to reduce casualties and the consequences caused by disasters. Providing disaster mitigation education to students from an early age is one of the initial efforts to raise community awareness of disasters. Early-grade students are the most vulnerable group to natural disasters. To address this issue, it is necessary to develop storybooks incorporating disaster mitigation materials. This study employed a descriptive quantitative method. Descriptive research aims to provide an overview of phenomena within a specific population. Data collection methods in this study focused on students through written tests. The research sample consisted of 30 fourth-grade elementary school students, with 10 students selected as the sample, along with three teachers. Data were collected through interviews, test questions, and questionnaires. Data analysis was conducted using a descriptive qualitative approach. The results of the study revealed that elementary school students’ reading literacy met the medium criteria, with an achievement percentage of 68.82%. The study suggests that parents should be more involved in their children's literacy education.